Pengaruh Pengetahuan Produk, Bagi Hasil dan Lokasi terhadap Preferensi Nasabah Pembiayaan Mudharabah di Bank Syariah Mandiri KCP Rancaekek - Bela Belian; M. Ryzki Wiryawan; Adi Indradi Wazdi (Jurnal Dimamu, 2022)
Based on the results of the initial research, that the background of this research is the fluctuating data of Mudharabah Financing Customers at Bank Syariah Mandiri KCP Rancaekek, causing fluctuations in Mudharabah Financing Customer Preferences at the Bank. This study aims to determine how the effect of product knowledge on customer preferences for Mudharabah Financing at Bank Syariah Mandiri KCP Rancaekek, knowing how the effect of profit sharing on customer preferences for Mudharabah Financing at Bank Syariah Mandiri KCP Rancaekek, and knowing how location influences customer preferences for Mudharabah Financing at the Bank. Syariah Mandiri KCP Rancaekek. The object of this research is the customers product knowledge, profit sharing, location and preferences of mudharabah financing customers at Bank Syariah Mandiri. The type of research is quantitative associative, the type of data is primary data and uses data collection techniques in the form of observations, interviews, literature studies, and questionnaire or questionnaire methods. Sampling with insedental sampling as many as 67 people. The results showed that there was an influence between product knowledge, profit sharing and location simultaneously on the preferences of mudharabah financing customers by 21% and the remaining 79% influenced by other variables not examined and the value of F count > F table = 5.567 > 2.17 with a significant level of 0 > 0.1 thus concluded that H0 is rejected and H1 is accepted.